Novel Agents in the Treatment of Unresectable Neuroendocrine Tumors - Oberstein, Paul E; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Pancreatic neuroendocrine tumors represent a small percentage of all pancreatic tumors (1.3%) but their incidence is rising. Prior to 2011, the only approved agent for unresectable disease was streptozicin (often used in combination with doxorubicin) but the efficacy of this drug is in question and there had not been any new drugs approved for this disease in more than 20 years. Recently there has been new excitement for the treatment of advanced neuroendocrine tumors including those of the pancreas (pNET) with FDA approval of 2 new agents in 2011. One of these agents was everolimus, an mTOR inhibitor, which was approved on the basis of a landmark phase III study (RADIANT-3). At the 2011 American Society of Clinical Oncology (ASCO) Annual Meeting, several abstracts were presented reviewing novel agents in the treatment of advanced NET. Three abstracts looked at characteristics of patients treated on the RADIANT-3 study and looked at the role of prior chemotherapy use (Abstract #4103), somatostatin analog use (Abstract #4010), and updated safety data (Abstract #4009) from this trial. Additionally, an abstract was presented (Abstract 4008) looking at updated data from the other targeted agent approved for advanced pNET, sunitinib, a multi-tyrosine kinase inhibitor, which demonstrated improvement in progression-free survival compared to placebo. Novel agents were also presented, including a phase II trial looking at the combination of sorafenib and bevacizumab (Abstract #4113), and a phase I trial looking at a novel somatostatin analog, pasireotide, in combination with everolimus (Abstract #4120) The authors review and summarize these abstracts in this article. Image: Mosaic on the wall of the 116th Street station on the 1st line of the New York subway system.